Cinnamoyl coA: NADP oxidoreductase-like 1 regulates abscisic acid response by modulating phaseic acid homeostasis in Arabidopsis thaliana. (28th October 2021) - Yin, Xiaoming; Bai, Ya-Li; Ye, Tiantian; Yu, Min; Wu, Yan; Feng, Yu-Qi
Abstract: Phaseic acid (PA), a main catabolite of abscisic acid (ABA), is structurally related to ABA and possesses ABA-like hormonal activity. However, the comprehensive metabolism pathway and roles of PA are not well understood. Here, using homologous alignment and expression pattern analysis, we identified in Arabidopsis the previously named CRL1 (Cinnamoyl coA: NADP oxidoreductase-like 1) as a PA reductase that catalyses PA to dihydrophaseic acid. The function of CRL1 and the potential role of PA were studied in transgenic CRL1 plants. Overexpression of CRL1 resulted in decreased ABA sensitivity in seed germination and attenuated drought tolerance. In contrast, increased ABA sensitivity and elevated drought tolerance was observed in down-regulated and loss-of-function crl1 mutants. Tyr162 in the conserved motif is the key residue in CRL1 to catalyse PA. Accelerated seed germination and earlier flowering phenotype were also observed in overexpressing lines, while retarded seed germination and delayed flowering occurred in crl1 mutants which accumulated more PA, but less dihydrophaseic acid than the wild type. This study demonstrates that PA plays diverse functions in drought tolerance, seed germination and flowering in an ABA-like manner, which may increase the adaptive plasticity of plants. Abstract : CRL1 plays important roles in ABA response and drought tolerance by regulating phaseic acid catabolism in Arabidopsis.